2015
DOI: 10.1093/cid/civ453
|View full text |Cite
|
Sign up to set email alerts
|

Study of Ebola Virus Disease Survivors in Guinea: Table 1.

Abstract: Ebola virus disease survivors frequently reported anorexia and arthralgia. Severity of arthralgia was related to lower functional recovery. There may be a role for focused screening and intervention for symptoms identified in this study of survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
103
4
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 34 publications
14
103
4
1
Order By: Relevance
“…The prevalence of arthralgias in our series is similar to that noted in a survey of survivors of EVD in Guinea (87%) a median of 103 days into convalescence, 14 but was higher than that reported in survivors of EVD at 21 months after the aforementioned Kikwit outbreak (48%) 11 and up to 29 months after the 2007 Bundibugyo outbreak (25%), perhaps suggesting attenuation over time. 13 Systematic clinical care for survivors of EVD was absent during the early part of the current outbreak due to the overwhelming need to care for those with acute disease.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The prevalence of arthralgias in our series is similar to that noted in a survey of survivors of EVD in Guinea (87%) a median of 103 days into convalescence, 14 but was higher than that reported in survivors of EVD at 21 months after the aforementioned Kikwit outbreak (48%) 11 and up to 29 months after the 2007 Bundibugyo outbreak (25%), perhaps suggesting attenuation over time. 13 Systematic clinical care for survivors of EVD was absent during the early part of the current outbreak due to the overwhelming need to care for those with acute disease.…”
Section: Discussionsupporting
confidence: 86%
“…7,[9][10][11]13 In the current outbreak, one qualitative study of 100 survivors in Sierra Leone reported blurred or partial loss of vision in convalescence but did not quantify these sequelae. 2 Surveys of 105 survivors in Guinea 14 and of 81 survivors in Sierra Leone 15 noted frequent musculoskeletal pain 14,15 and visual problems; 15 neither study included a clinical examination of survey participants. No studies from the west African outbreak have examined possible relations between features of acute EVD and the frequency or severity of clinical sequelae.…”
Section: Introductionmentioning
confidence: 99%
“…One recent study of Guinean survivors from the recent outbreak used a questionnaire administered either in person or over the telephone to collect data on a variety of persistent or new symptoms, and many of the questions focused on neurologic and psychiatric impairments since discharge from the ETU [36]. While the study was limited by the questionnaire design and the lack of neurologic examinations, neurologic symptoms were reported in a substantial number of participants during the subacute convalescent period (defined as 91-210 days) and included difficulty with concentration (37.5%) or memory (21.3%), headache (29.2%), or dizziness (6.3%).…”
Section: Clinical Sequelaementioning
confidence: 99%
“…A recent study analyzed 105 EVD survivors approximately 3.5 months post-discharge from a Guinea treatment unit [7]. Anorexia (100%), chest (31%), joint (87%) and back pain (46%), and myalgias (27%) were reported.…”
Section: Fatigue and Musculoskeletal Painmentioning
confidence: 99%
“…Those who had joint and muscle pain during convalescence also suffered from similar symptoms during acute EVD. Disseminated intravascular coagulation and elevated D-dimers have been detected in the acute stage of infection, and could also play a role in the pathogenesis of late osteoarticular lesions [7].…”
Section: Pathogenesismentioning
confidence: 99%